Androgen response to social competition in a shoaling fish - Teles, Magda (2016)
Androgens respond to social challenges and this response has been interpreted as a way for males to adjust androgen-dependent behavior to social context. However, the androgen responsiveness to social challenges varies across species and a conceptual framework has been developed to explain this variation according to differences in the mating system and parental care type, which determines the regimen of challenges males are exposed to, and concomitantly the scope (defined as the difference between the physiological maximum and the baseline levels) of response to a social challenge. However, this framework has been focused on territorial species and no clear predictions have been made to gregarious species (e.g. shoaling fish), which although tolerating same-sex individuals may also exhibit intra-sexual competition. In this paper we extend the scope of this conceptual framework to shoaling fish by studying the endocrine response of zebrafish (Danio rerio) to social challenges. Male zebrafish exposed to real opponent agonistic interactions exhibited an increase in androgen levels (11-ketotestosterone both in Winners and Losers and testosterone in Losers). This response was absent in Mirror-fighters, that expressed similar levels of aggressive behavior to those of winners, suggesting that this response is not a mere reflex of heightened aggressive motivation. Cortisol levels were also measured and indicated an activation of the hypothalamic-pituitary-interrenal axis in Winners of real opponent fighters, but not Losers or in Mirror-fighters. These results confirm that gregarious species also exhibit an endocrine response to an acute social challenge.